Electric field emitted by a particle track in two semi-infinite media - García-Fernández, Daniel; Dallier, Richard; Escudie, Antony; Martin, Lilian; Revenu, Benoît (Proceedings of Science, 2019)
The radio technique for the detection of cosmic rays is nowadays a well-established experimental technique, and several projects intend to adapt it for the detection of neutrinos. When a primary particle interacts with a target particle in a medium, a shower containing electrically charged particles is created, and an electric field is emitted. The measurement and analysis of this electric field can reveal the properties of the primary particle. In order to be able to produce an accurate reconstruction of the properties of the primary particle, a reliable calculation of the electric field is needed. Although almost every current radio detection experiment is located near a boundary (e.g. ground), the effect of this boundary on the calculation of the electric field is either not taken into account or the field is decomposed into direct, reflected and transmitted components, which is a correct description in the far-field approximation only. When the emitting shower and the detector are close to the boundary with respect to the observation wavelength, this approximation breaks down, as it is the case for the EXTASIS experiment when the particles are near ground level. We present in this work a frequency-domain calculation of the electric field from a charged particle track lying in two semi-infinite media separated by a planar boundary. We also give an estimate of the expected signal from a full air shower using a toy model.
CRIS-Team Scopus Importer:2024-12-16